Studi Empiris: Pengaruh Kualitas Layanan Terhadap Loyalitas Anggota KSPPS Mitra Mandiri - Rika Hasanah; Indra Hastuti; Agus Suyatno (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This research aims to find out whether service quality, trust and promotions influence member loyalty. The type of data in this research is quantitative in the form of a questionnaire and analyzed using the SPSS 26 program. The respondents for this research were 98 cooperative members. In research during the observation period it shows a normal distribution. Based on the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, no deviations were found from the basic assumptions, in other words the data used met the requirements for using the multiple linear regression equation model. The research results show that the variables of service quality, trust and promotion have a significant and simultaneous positive effect on the member loyalty variable.